Analisis Kognitif pada Soal Buatan Guru Kelas XII Mata Pelajaran Bahasa Indonesia di SMK Kerabat Kita Bumiayu - Wildan Dimas Prayitno; Cintya Nurika Irma; Esti Tri Yuni Rahayu (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to explore the cognitive aspects of questions developed by the Indonesian language teacher at Sekolah Menengah Kejuruan (SMK) Kerabat Kita Bumiayu. Through an interview conducted with the subject teacher in January 2024 at SMK Kerabat Kita Bumiayu, it was found that the design of the questions had considered Bloom’s Taxonomy, specifically the cognitive domain. In order to assess students' abilities, an appropriate evaluation process is necessary. The assessment serves to explore the extent of students’ comprehension of the material delivered during the learning process. This research employs a qualitative method. It adopts an evaluative approach to learning assessment based on Bloom’s Taxonomy, with a particular focus on the cognitive domain. Data analysis was carried out through three stages: the first is data reduction, which aims to simplify information obtained from observation, interviews, and documentation; the second is data presentation, where the reduced data are organized into a simpler and more narrative format.The data analyzed in this study consist of four essay questions designed by the Indonesian language teacher for grade XII students at SMK Kerabat Kita Bumiayu. The research focuses on observing the cognitive level reflected in the essay questions used in the Mid-Semester Assessment (Penilaian Tengah Semester/PTS).